ANALYSIS OF METAPHORS FOUND ON THE DIALOGUES OF “THE TRAGEDY OF OTHELLO THE MOOR VENICE” DRAMA SCRIPT BY WILLIAM SHAKESPEARE - Koni Aprilia (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2019)
Communication can be built if there is an understanding between speaker and the hearer. This study aims to analyze the metaphors found on drama script, although drama represents  human’s communication but the language used is not the same as the language used in daily communication, usually the drama script uses language style and ambiguous.The objectives of the study are to know what types and meaning of metaphors found on the dialogue of “the Tragedy of Othello the Moor Venice” drama script by William ShakespeareThe type of this research is a descriptive qualitative research. The data collection was started by observing the drama script and classify into each type then the writer also specify the data which will be analyzed. The data analysis was started by finding the metaphors on the dialogue of drama script, identifying the types of metaphors based on Lakoff and Johnson theory (2003) and interpret the data through its logical meaning.The result of this research shows there are 25 data metaphors found on the text. They are divided into 60% of structural metaphors, 20% of orientational metaphors, 12% of container ontological metaphors and 8% of personification ontological metaphors. Second, the meaning of metaphors found on the drama script also revealed from the analysis process which shows the condition of the Venice such as; love, loyalty, betrayal, envy,  racism, manipulation, power competition and social status. Metaphors has been used as a tool in communication in order to illustrates the meaning with a greater emotion. Keywords : semantics, metaphor, drama script